2020
DOI: 10.4103/ajns.ajns_289_19
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of pineal region arachnoid cyst: A case report and review of literature

Abstract: Arachnoid cyst is a rare benign cerebrospinal fluid-filled cyst that can develop anywhere in the brain along the arachnoid membrane and usually unaccompanied by the anomalous development of the brain structure. These cysts are usually located in the middle cranial fossa. However, they are also denoted in other regions. Arachnoid cysts are mostly asymptomatic and diagnosed incidentally. Spontaneous regression of arachnoid cysts in different anatomical regions of the brain has been reported in the literature. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Ammar et al reviewed cases of spontaneously resolved ACs prior to 2020 and found that up to 85% of cases occurred in children. 4 To date, only one case of spontaneous resolution of a CPA AC has been reported in an 11-month-old child by Takagi et al 5 Our case represents the first documented case of a symptomatic CPA AC resolved without intervention in an adult.…”
Section: Spontaneous Resolution Of Acs In Various Locations Has Beenmentioning
confidence: 59%
See 1 more Smart Citation
“…Ammar et al reviewed cases of spontaneously resolved ACs prior to 2020 and found that up to 85% of cases occurred in children. 4 To date, only one case of spontaneous resolution of a CPA AC has been reported in an 11-month-old child by Takagi et al 5 Our case represents the first documented case of a symptomatic CPA AC resolved without intervention in an adult.…”
Section: Spontaneous Resolution Of Acs In Various Locations Has Beenmentioning
confidence: 59%
“…reported in the literature. 3,4 Most reported cases occur in children and involved the supratentorial region. Ammar et al reviewed cases of spontaneously resolved ACs prior to 2020 and found that up to 85% of cases occurred in children.…”
Section: Spontaneous Resolution Of Acs In Various Locations Has Beenmentioning
confidence: 99%
“…However, it is worth noting that spontaneous resolution, expansion, and rupture of cysts have all been reported. [13][14][15] Although there is a lack of class I evidence regarding the optimal treatment of arachnoid cysts, it is generally agreed that if the cyst is symptomatic due to the presence of hydrocephalus, neurological deficits, or localized seizures, surgical management is indicated. For asymptomatic cysts, observation is recommended, although the benefit of repeat imaging past the age of 4 years is controversial.…”
Section: Discussionmentioning
confidence: 99%